A Moist Entropy Budget View of the South Asian Summer Monsoon Onset. Issue 8 (16th April 2019) - Ma, Ding; Sobel, Adam H.; Kuang, Zhiming; Singh, Martin S.; Nie, Ji
Abstract: Using a high‐resolution global model with explicit representation of convection, the physical processes involved in the abrupt onset of South Asian summer monsoon are investigated within a moist entropy budget framework. The monsoon onset is a two‐stage transition. During the first stage, which starts around 2 months before onset, the source terms of column‐integrated moist entropy gradually increase, while the export by the large‐scale circulation slowly strengthens. The second stage is marked by a sudden increase of radiative heating and surface latent heat flux 10 days prior to the onset, followed by abrupt strengthening of large‐scale export of moist entropy. When either cloud‐radiative or wind‐evaporation feedback is disabled in numerical experiments, the monsoon experiences much smoother and weaker onset. The evolution of the system in a gross moist stability plane demonstrates that these positive feedbacks destabilize the system and are responsible for the abruptness of the transition. Key Points: The evolution of moist entropy through monsoon onset features two distinct stages: gradual accumulation and abrupt increase The onset of the South Asian summer monsoon is marked by a sudden increase in radiative heating and surface latent flux Without cloud‐radiative and wind‐evaporation feedbacks, the monsoon experiences much smoother onset